Анатомо-физиологические основы видообразования пресмыкающихся - Стрельников, И.Д. (Вестник зоологии, 1968)
The author presents the results of an investigation of the value of interrelation and interconditionality of the dimensions (weight) of the body, brain and metabolism energy in the reptile species formation. Both in the ontogenesis of the species representatives of the class and in their dimension series (from the smallest to the biggest) the relative size (weight) of the brain in general is the more, the less is the size (weight) of the body, and vice versa (Fig. 1 and 2). A number of genera and species in the class and orders of the reptiles is the more, the less are the dimensions (weight) of the body and the more is the relative weight of the brain of the species representatives of the size groups of the reptiles, and vice versa with the increase of a body dimensions a number of genera and species and the relative weight of the brain decrease within the limits of a class (Fig. 3 and 5). The fact that in the genera of snake not the smallest animals are represented by the greatest number of genera and species is probably, con-nected with the peculiarities of the structure of somewhat bigger forms, the dynamics of their movement, in particular, with the greater speed, strength and dexterity when pursueing, seizing and swallowing the prey as a whole. In reptiles as well as in other vertebrates a non-linear dependence is observed between the dimensions (weight) of the body, brain and a number of genera and species.